Analisis Jual Beli Online dalam Persfektif Agama Islam - Riza Deliyani Harahap; Salmida Siregar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The purpose of this study is to analyze buying and selling from the perspective of Islam. Where we know that the rapid development of science and technology has brought positive and negative impacts on various areas of life. Nothing but the most influential is the field of economics. Now the development of science and technology has provided new ways of trading, one of which is buying and selling online. As a result, researchers are interested in investigating Islamic perspectives on online selling practices. This research uses qualitative research techniques and literature studies. This study used primary and secondary data through interviews and reviews of articles, books and journals related to the topic.